Investigating Heat Transfer in Whole-Body Cryotherapy: A 3D Thermodynamic Modeling Approach with Participant Variability - Elfahem, Rim; Bouchet, Bastien; Abbes, Boussad; Legrand, Fabien; Polidori, Guillaume; Beaumont, Fabien (Fluids, 2024)
Whole-body cryotherapy (WBC) is a therapeutic practice involving brief exposure to extreme cold, typically lasting one to four minutes. Given that WBC sessions often occur in groups, there is a hypothesis that cumulative heat dissipation from the group significantly affects the thermo-aerodynamic conditions of the cryotherapy chamber. Computational fluid dynamics (CFD) is employed to investigate thermal exchanges between three subjects (one man, two women) and a cryotherapy chamber at −92 °C during a 3-minute session. The investigation reveals that collective body heat loss significantly influences temperature fields within the cabin, causing global modifications in aerodynamic and thermal conditions. For example, a temperature difference of 6.7 °C was calculated between the average temperature in a cryotherapy chamber with a single subject and that with three subjects. A notable finding is that, under an identical protocol, the thermal response varies among individuals based on their position in the chamber. The aerodynamic and thermal characteristics of the cryotherapy chamber impact the heat released at the body’s surface and the skin-cooling rate needed to achieve recommended analgesic thresholds. This study highlights the complexity of physiological responses in WBC and emphasizes the importance of considering individual positions within the chamber for optimizing therapeutic benefits.
Keywords: aerodynamic; computational fluid dynamics (CFD); heat transfer; thermal plume; whole body cryotherapy (WBC)